2015
DOI: 10.1071/bt14235
|View full text |Cite
|
Sign up to set email alerts
|

Calcium : magnesium ratio affects environmental stress sensitivity in the serpentine-endemic Alyssum inflatum (Brassicaceae)

Abstract: Plants endemic to serpentine soils are adapted to harsh environmental conditions typical of those soils, particularly, low (<1) calcium (Ca) : magnesium (Mg) ratios. We compared survival of two perennial Alyssum species native to Iran under experimental manipulations of Ca : Mg ratio, including when Ca : Mg ratio was varied under conditions of high ammonium concentration and heat stress. Alyssum inflatum is a serpentine endemic capable of nickel (Ni) hyperaccumulation, whereas A. lanceolatum is found on non-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Serpentine soils are shown to have the lowest concentration of soluble calcium and the highest concentration of soluble magnesium for all species analyzed (Table 3). According to Ghasemi et al [27], the Ca:Mg-ratios in the serpentine soils in our experiment (ranging from 1.6-2.2:1, Table 3) should be close to the developmental optimum for serpentine endemic Brassicaceae. The standard and calcareous soils have much higher Ca:Mg-ratios (ca.…”
Section: Soil Analyses and Cultivated Plantssupporting
confidence: 72%
See 1 more Smart Citation
“…Serpentine soils are shown to have the lowest concentration of soluble calcium and the highest concentration of soluble magnesium for all species analyzed (Table 3). According to Ghasemi et al [27], the Ca:Mg-ratios in the serpentine soils in our experiment (ranging from 1.6-2.2:1, Table 3) should be close to the developmental optimum for serpentine endemic Brassicaceae. The standard and calcareous soils have much higher Ca:Mg-ratios (ca.…”
Section: Soil Analyses and Cultivated Plantssupporting
confidence: 72%
“…Loew and May [ 26 ] were the first to study the influence of calcium and magnesium on the plant productivity of serpentine substrates and concluded that for optimal growth, the calcium to magnesium ratio must at least be equal. Physiologically, serpentine plants are able to react to Ca-deficiency by inverting the Ca:Mg ratio to values ≥1 within their tissues [ 24 , 27 ]. This is associated with one or more of the following adaptive mechanisms: tolerance of Ca deficiency and/or Mg toxicity, selectivity (ability to take up Ca in the presence of high concentrations of Mg) and luxury consumption of Mg (storage for later use; [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both Ni exclusion and Ca accumulation are likely to account for several adaptation mechanisms evolved by the serpentine populations of S. paradoxa. In particular, the latter mechanism is a well-known strategy used to maintain adequate internal concentrations of Ca at the low Ca/Mg ratios typical of serpentine soils (Wallace et al 1982;Tibbetts and Smith 1993;Asemaneh et al 2007, Ghasemi et al 2015. In the serpentine populations of S. paradoxa, the great Ca acquisition was responsible for the reversal of the Ca/Mg ratio in the plant tissue compared with the soil, which is a trait already found in other serpentinophytes (Bettarini et al 2019;Mengoni et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…However, edaphic specialists and other plant species restricted to special soils are particularly sensitive to habitat loss and climate change, because of their small population sizes and habitat specialization ( Damschen et al. 2010 , 2012 ; Ghasemi et al. 2015 ).…”
Section: Introductionmentioning
confidence: 99%